Young Muslim America: Faith, Community, and Belonging - Muna Ali (Oxford University Press, 2018)
Young Muslim America explores the perspectives and identities of the American descendants of immigrant Muslims and converts to Islam. Whether their parents were new Muslims or new Americans, the younger generations of Muslim Americans grow up bearing a dual heritage and are uniquely positioned to expound the meaning of both.